Canine lymphoma and vector‐borne diseases: Molecular and serological evaluation of a possible complicity - Henriques, Joaquim (2021)
Lymphoma is the most common haematological malignancy in dogs and its aetiology is largely unknown. The presence of canine vector-borne agents (CVBD) in lymphoma tissues has been described and its causative effects questioned. We intended to evaluate the presence and extent of Leishmania infantum, Ehrlichia canis, Anaplasma phagocytophilum and Bartonella henselae infection in dogs with lymphoma. Sixty-one dogs, living in the Lisbon metropolitan area, with a diagnosis of lymphoma were enrolled. Immunofluorescence assays were used to detect serum IgG's. The presence of DNA from CVBD agents in tumour tissue was assessed by PCR. All dogs tested negative for B. henselae, A. phagocytophilum and E. canis by both serology and PCR. Regarding L. infantum, 8.2% (n = 5) of the dogs had a positive serologic result. L. infantum DNA was detected in two samples of diffuse large B-cell lymphoma (DLBCL). These results show an increased, but not significant, seropositivity (8.2% vs 7.9%) and molecular detection (3.3% vs 1.2%) for L. infantum in dogs with lymphoma, when compared to the reported canine population in the same geographical area. We could not identify an association between lymphoma and E. canis, A. phagocytophilum, B. henselae or Leishmania infantum infection in the studied population. Nevertheless, further studies, following dogs trough their CVBD disease evolution, are worthwhile and may help clarify a possible role of CVBD agents in lymphomagenesis.